Multitemporal Analysis of Coastal Erosion Based on Multisource Satellite Images in the South of the Mono Transboundary Biosphere Reserve in Togo (West Africa) - (:unkn) unknown (My University, 2018)
Climate change is affecting terrestrial and maritime ecosystems of Mono transboundary biosphere reserve and the whole Togolese coast. This research focuses both on the dynamics of the barrier beach and on spatial and temporal changes that affected the ocean coastline and its adjacent Lake Togo and Lake Boko during the period 1988-2018. The methodological approach adopted is based on a combination of optical and radar remote sensing. As results, the Lake Togo widened on average by 1.55 m/year while the coastline of the Lake Boko shrank by 1.25 m/year. For the coastline of the Ocean, the regression ranged from 1.66 to 5.25 m/year. The barrier beach experienced an average immersion of 9.25 ha/year. Predictions on the basis of the average rate of immersion of the barrier beach of 9.25 ha/year showed that the latter is exposed to a continuous immersion hazard that would affect more than 7% of its current area (6557.33 ha) by the year 2070.
Keywords: African Research